(untitled) (Journal of Economic Research & Business Administration, 2021)
In recent times, globalization has raised issues on dynamics of economic globalization, financial deepening and energy consumption. The present study has been an attempt to explore interlinks between these variables using Toda-Yamamoto causal approach and ARDL bound cointegration approach. The results showed unidirectional causality run from globalization to financial deepening variables such as credit to private sector and market capitalization. It is also observed that unidirectional causality runs from credit to private sector to energy consumption. No causal relationship runs from broad money supply to globalization and energy consumption. The coefficient of globalization has a positive and statistically significant effect on energy consumption for both short and long-run. The results also shows that financial deepening has impact on energy consumption in Nigeria; the coefficients on the interaction between the globalization (GLS), broad money supply (BDS), credit to private sector (CPS) and market capitalization (MCP) are statistically significant at 5% level and with the positive sign in the short-run and negative sign in the long –run. Nigeria should develop its financial sector to enhance investment in energy saving equipments to reduce fossil fuel consumption. Key words: Globalization, Financial development, Energy Consumption.